Phenotypes of successful living among adolescents with HIV in Rwanda: a latent profile analysis - Dieudonne Kayiranga; Darius Gishoma; Gallican Rwibasira; Eric Remera; Donatilla Mukamana; Michael V. Relf; Wei Pan (BMC Public Health)
Abstract Background HIV remains a major public health concern globally, and 85% of adolescents with HIV (AWH) live in Sub-Saharan Africa (SSA). Despite advances in treatment and prevention efforts, adolescents continue to be disproportionately affected by HIV and are a group with poor adherence to antiretroviral medication. We identified phenotypes of successful living among adolescents with HIV in Rwanda. Methods A multi-stage stratified random sampling was used to collect data from 300 AWH using a validated and piloted questionnaire from four provinces and Kigali City in Rwanda. Data were collected in August 2023 and were analyzed using latent profile analysis (LPA). The following variables were computed to measure their associations and determine the latent profiles (or phenotypes) of successful living: viral load, number of sex partners in a lifetime, condom use during sex, adherence to HIV antiretroviral therapy, HIV stigma, depressive symptoms, state of hope, self-esteem, resilience, disclosure, HIV quality of life, and perceived social support. Results The two distinct profiles of successful living among adolescents with HIV were identified through LPA: 46% of adolescents struggled to live with HIV (the first profile) while 54% of adolescents lived successfully with HIV (the second profile). There are several factors associated with successful living among AWH. Successful living was positively associated with spirituality, residing with family members, a stable home environment, psychological well-being, social support, and acquiring HIV through vertical transmission. The adherence to ART, HIV-related stigma, levels of depression, hope, self-esteem, resilience, availability of social support, and patterns of disclosure of HIV status are determinants of adolescents’ experiences of living with HIV. Additionally, adolescents tend to struggle to live with HIV in late adolescence, especially when the factors associated with successful living are not met. Conclusions This study identified two profiles of Successful Living among AWH. Our results suggest developing profile-oriented, tailored interventions to improve the quality of life and health outcomes of AWH.